(untitled) (Texas Journal of Medical Science, 2025)
Cardiomyopathy is a group of diseases characterized by primary or secondary damage to the heart muscle, leading to impaired mechanical or electrical functions of the heart. This disease occurs in different forms: dilated, hypertrophic, restrictive, and arrhythmogenic right ventricular dysplasia. Cardiomyopathy can be accompanied by heart failure, arrhythmias and thromboembolic complications. The etiology of the disease may be related to genetic, infectious, toxic, autoimmune or metabolic factors. Clinical symptoms include shortness of breath, fatigue, palpitations, and edema. Treatment options include medications (ACE-inhibitors, beta-blockers, diuretics), invasive procedures (ICD, CRT, heart transplant), and lifestyle changes. Prevention includes heart health care, risk factor management, and regular checkups. Early detection and treatment of cardiomyopathy is important in improving the patient’s quality of life and reducing complications